2017
DOI: 10.1111/dme.13357
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by physicians when discussing the Type 2 diabetes diagnosis with patients: insights from a cross‐national study (IntroDia®)

Abstract: Globally, most physicians indicated that conversations with patients at diagnosis of Type 2 diabetes strongly influence patient self-care. Higher physician empathy was associated with fewer challenges during the diagnosis conversation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Themes 4 and 5 describe opposite types of relationships with HCPs, although both types can unintentionally affect patients' willingness to attend SDE. Recent results of the large IntroDia survey showed that 73% of 6,753 physicians surveyed agreed that the conversation at diagnosis of type 2 diabetes affects patients' acceptance of their condition and subsequent quality of self-care (28).…”
Section: Discussionmentioning
confidence: 99%
“…Themes 4 and 5 describe opposite types of relationships with HCPs, although both types can unintentionally affect patients' willingness to attend SDE. Recent results of the large IntroDia survey showed that 73% of 6,753 physicians surveyed agreed that the conversation at diagnosis of type 2 diabetes affects patients' acceptance of their condition and subsequent quality of self-care (28).…”
Section: Discussionmentioning
confidence: 99%
“…The commonest reasons for non-attendance were competing demands on the time of the participants. This highlights the importance of the way education and its value is communicated to people with diabetes, a theme also picked up in the paper by Capehorn et al [5].…”
mentioning
confidence: 74%
“…This highlights the importance of the way education and its value is communicated to people with diabetes, a theme also picked up in the paper by Capehorn et al . .…”
mentioning
confidence: 99%
“…This relationship gives patients the necessary support and tools to have successful disease outcomes. Studies [28,29,30] have suggested that positive patient–provider relationships influence adaptation through mechanisms of increased support and improved communication with the provider.…”
Section: Methodsmentioning
confidence: 99%